Optimasi Proses Overproduksi, Pemurnian dan Karakterisasi Protein Mga Sebagai Molekul Target Untuk Pencegahan Infeksi oleh Streptococcus Pyogenes - Muhaimin Muhaimin; Oei Ban Liang; Enny Ratnaningsih; Endang Purwantini; Debbie Soefie Retnoningrum (Jurnal Matematika & Sains, 2003)
Optimization of overproduction, purification and characterization of Streptococcus pyogenesâs Mga recombinant protein from Escherichia coli pMALMga carrying mga49 gene had been carried out. The overproduction optimization was conducted by culturing the Escherichia coli pMALMga of OD600 = 0,7 in LB medium with or without glucose, and induced by 0,3 mM IPTG for a certain period of time. The protein produced was MBP-Mga fusion protein with a molecular weight of about 104 kDa. The purification was conducted by affinity chromatography using amylose ligands at pH 7,4 and continued by SDS-PAGE. One band identified at 104 kDa showed that the MBP-Mga fusion protein was pure enough for further analysis. The MBP-Mga protein was then injected into rabbit to produce polyclonal antibodies. The antibody development was monitored by dot blot and Western blot. The antibodies produced gave a positive reaction to MBP-Mga fusion protein. Adsorption and precipitation of the polyclonal antibodies which gave a positive reaction to MBP protein was done by adding pure MBP protein (56 kDa) produced by Escherichia coli pMALc2, and purified by affinity chromatography using amylose ligands at pH 7,4. The results showed that the antibodies gave a positive reaction to Mga recombinant protein and a negative reaction to MBP recombinant protein.